Active labour market policy as a socialising agent: a cross-national analysis of learning attitudes. Issue 1 (2nd January 2020) - Benda, Luc; Koster, Ferry; van der Veen, Romke
ABSTRACT: Most active labour market policy (ALMP) research investigates potential socioeconomic consequences such as unemployment risks and earning potential but too often neglects potential cultural effects. When approaching ALMP research based on institutional and socialisation theory, researchers would expect that people internalise cultural and normative elements from their institutional environment. This study discusses the influence of country-level ALMP training programme effort on the learning attitude of people by considering participants own educational and familial background. Only ALMP training programme effort is studied because this type of programme is directly aimed at active learning. This study presents an analysis of macro-level data from the OECD on labour market policy spending combined with micro-level data from the PIAAC, totalling 64, 150 observations from 19 countries. The results show that people who have higher education credentials or have more highly educated parents have on average a more proactive learning attitude. These differences tend to be smaller in countries that put more effort in ALMP training programmes. People with less education or who have lesser educated parents tend to have a more proactive learning attitude in countries that put more effort in ALMP training programmes compared to their equals in countries that put in less effort.